ANALISIS TINGKAT PEMAHAMAN PENGETAHUAN AGAMA ISLAM MASYARAKAT SUKU ANAK DALAM (SAD) DI KABUPATEN MUSIRAWAS UTARA SUMATERA SELATAN - Hendra Harmi (Akademika : Jurnal Teknologi Pendidikan, 2022)
This study aims to analyze the level of understanding of Islam in the Suku Anak Dalam (SAD) community in Muratara Regency, South Sumatra. This research is a type of survey research. The population taken in this study is the entire SAD community in Muratara Regency, South Sumatra. The sampling technique used was purposive sampling with 56 data samples consisting of 27 women and 29 men in 3 villages, namely Sungai Jernih, Sungai Kijang and Kerta Dewa. The data collection technique used a non-test technique in the form of filling out a questionnaire. The instrument used in this study is a questionnaire sheet using a modified Likert scale with 4 answer choices. The results of the validity and reliability test showed that the instrument used was valid and reliable. For the results of the analysis, the percentage for each respondent from the SAD community in Muratara Regency, South Sumatra is in the range of 76-100% which is in the category of strongly agree based on the Likert scale interpretation table. This means that all respondents strongly agree with the statements regarding indicators of religious understanding proposed in the questionnaire. This shows that the Suku Anak Dalam (SAD) people in 3 villages in the Muratara Regency Regency, South Sumatra have a good understanding of religion